2015
DOI: 10.1051/0004-6361/201526128
|View full text |Cite
|
Sign up to set email alerts
|

IRIS observations of the Mg ii h and k lines during a solar flare

Abstract: The bulk of the radiative output of a solar flare is emitted from the chromosphere, which produces enhancements in the optical and UV continuum, and in many lines, both optically thick and thin. We have, until very recently, lacked observations of two of the strongest of these lines: the Mg ii h and k resonance lines. We present a detailed study of the response of these lines to a solar flare. The spatial and temporal behaviour of the integrated intensities, k/h line ratios, line of sight velocities, line widt… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
86
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(96 citation statements)
references
References 38 publications
(70 reference statements)
8
86
2
Order By: Relevance
“…These spectral features are optically thick and often show a strong reversal in the core of the line (e.g., Schmit et al 2015). As we will see, the profiles are not reversed during this flare and the Gaussian moment is an adequate description of the line profile (the lack of a reversal during flaring conditions has been reported previously by Kerr et al 2015 andLiu et al 2015). We take the rest wavelengths for the doublet, 2796.354 Å for the k-line and 2803.531 Å for the h-line, from Murphy & Berengut (2014).…”
Section: Observations Of the Flare Footpointssupporting
confidence: 76%
“…These spectral features are optically thick and often show a strong reversal in the core of the line (e.g., Schmit et al 2015). As we will see, the profiles are not reversed during this flare and the Gaussian moment is an adequate description of the line profile (the lack of a reversal during flaring conditions has been reported previously by Kerr et al 2015 andLiu et al 2015). We take the rest wavelengths for the doublet, 2796.354 Å for the k-line and 2803.531 Å for the h-line, from Murphy & Berengut (2014).…”
Section: Observations Of the Flare Footpointssupporting
confidence: 76%
“…The ratio at footpoint pixels along all eight slits is around 1.1 (with a standard deviation, σ = 0.068) and does not change during the flare. This is consistent with previous flare observation by OSO-8/LPSP (Lemaire, Choucq-Bruston, and Vial, 1984) and an M class flare observed by IRIS and analyzed by Kerr et al (2015), who found the k to h ratio is 1.07 to 1.19 in flaring pixels and does not change much during flare. Figure 10 shows that there are variations of the k to h ratio at pixels 470-550 before the impulsive phase of the flare and during the flare.…”
Section: Evolution Of Mg II Spectra During the X1 Flaresupporting
confidence: 93%
“…During the observed flare, the LPSP spectrometer was also able to detect an enhanced emission in three subordinate (intersystem) Mg ii lines, which have wavelengths around the Mg ii k line and appear as absorption lines in the quietSun (QS) spectrum. With the observations from IRIS, the Mg ii lines during an M class flare was studied in detail by Kerr et al (2015). They investigated the spatial and temporal behaviour of Mg ii lines and found there were red shifts of line centroids, line broadening, and blue asymmetries in flare ribbons.…”
Section: Introductionmentioning
confidence: 99%
“…Several important characteristics are inferred: (1) in general, the spectra of the ordinary flare ribbon behind the front are brighter than those on the negative front; (2) strong, mainly redshifted emission and line broadening (with a FWHM near or greater than 0.8 Å) are found in the negative front relative to the ribbon behind; and (3) both the Mg II and C II show a central reversal pattern in the ribbon front. This is a common feature for quiet Sun spectra (Leenaarts et al 2013) but unusual for flare regions (Kerr et al 2015).…”
Section: Iris Imaging Spectroscopy Of the Event On 2014 Augustmentioning
confidence: 83%